Re-examination of "release-from-PI" phenomena: recall accuracy does not recover after a semantic switch. Issue 9 (21st October 2018) - Hubbard, Nicholas A.; Weaver, Travis P.; Turner, Monroe P.; Rypma, Bart
ABSTRACT: Recall accuracy decreases over successive memory trials using similar memoranda. This effect reflects proactive interference (PI) – the tendency for previously studied information to reduce recall of new information. However, recall improves if memoranda for a subsequent trial are semantically dissimilar from the previous trials. This improvement is thought to reflect a release from PI. We tested whether PI is reduced or released from the semantic category for which it had been induced by employing paradigms which featured inducement, semantic switch, and then return-to-original category epochs. Two experiments confirmed that PI was not released after various semantic switch trials (effects from d = −0.93 to −1.6). Combined analyses from both studies demonstrated that the number of intervening new category trials did not reduce or release PI. In fact, in all conditions recall accuracy decreased, demonstrating that PI is maintained and can increase after the new category trials. The release-from-PI account cannot accommodate these broader dynamics of PI. This account is also incongruent with evidence and theory from cognitive psychology, linguistics, and neuroscience. We propose a reintroduction-of-PI account which explains these broader PI dynamics and is consistent with the wider psychological and neurosciences.